THE ROLE OF MSMEs IN IMPROVING THE ECONOMY IN RAMADAN - Muhammad Ade Kurnia Harahap; Sutrisno Sutrisno; Itot Bian Raharjo; Rini Novianti; Abu Muna Almaududi Ausat (Universitas Pahlawan Tuanku Tambusai, 2023)
Ramadan is a very important month for Muslims around the world. It is considered a holy month, where Muslims fast, worship, and give good deeds. In addition, the month of Ramadan is also an important moment for most businesses, especially MSMEs. This study aims to analyse the role of MSMEs in improving the economy in the month of Ramadan and what factors influence their success in taking advantage of this moment. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of this study concluded that MSMEs have an important role in improving the economy during Ramadan. MSMEs can increase community consumption and income, create jobs, and encourage economic growth. To increase the role of MSMEs in improving the economy during Ramadan, MSMEs need to carry out several strategies such as improving product and service quality, optimising marketing, improving operational efficiency, innovating and adapting to changes in trends and demand, as well as expanding networks and collaborating with other parties.